Valeur énergétique de la chair de l'huître Crassostrea gigas estimée par mesures microcalorimétriques et par dosages biochimiques - Heral, Maurice; Deslous Paoli, Jean-marc (Gauthier-villars, 1983)
The energetic values measured by the direct method and estimated by biochemical analysis of the annual cycle of ash-free dry weight of two Crassostrea gigas populations, show that the analytic results are inferior by 30% to those obtained by direct evaluation. The mean energetic amount is 4.84 cal.mg-1. Its seasonal variations, from 4.11 to 5.39 cal.mg-l, mainly depend on variations in the values of lipids. The mean conversion factor of lipids is 8.63 cal.mg-!, noticeably different from Brody's (9.45 caI.mg-I). This coefficient varies according to seasons from 7.85 to 9.38 cal.mg'-I. According to the biochemical evaluations, female oysters appear to he more energetic than male oysters when gonads are full. Direct evaluations, on the other hand, show no significant differences between sexes. These divergent results may he due to differences in the specific composition of fatty acids. The reproduction effort increases with age, and is responsible for a loss of energy of 18% for one year-old oysters, and 63% for two year-old oysters. Consequently, younger oysters will devote their energetic metabolism to growth, and two year-old oysters will preferably use their energy, during the summer period, for reproduction. La valeur énergétique mesurée par la méthode directe et estimée par les dosages biochimiques du cycle annuel de la chair sans cendre de deux populations d'huîtres Crassostrea gigas, met en évidence que l'estimation biochimique est inférieure de 30% à une estimation directe. La valeur énergétique moyenne est de 4,84 cal-mg -1. Ses variations saisonnières de 4,11 à 5,39 caI.mg-t, sont dues principalement aux fluctuations des valeurs en lipides. Le coefficient moyen de conversion pour les lipides est de 8,63 caI.mg-l; il est sensiblement différent de celui de Brody (9,45 caI.mg-I). Ce coefficient varie selon les saisons de 7,85 à 9,38 cal.mg-I. Lors de la réplétion maximale des gonades, les huîtres femelles semblent plus énergétiques que les huîtres mâles, du moins à partir des estimations biochimiques. Par ...